The role of information sharing in modulating the effect of financial access on inequality - Vanessa Simen Tchamyou (African Governance and Development Institute (AGDI), 2018)
This study examines the role of information sharing in modulating the effect of financial access on income inequality in 48 African countries for the period 2004-2014. Information sharing is proxied with private credit bureaus and public credit registries. All dynamics of financial development are taken into account, namely: depth (money supply and liquid liabilities), efficiency (at banking and financial system levels), activity (from banking and financial system perspective) and size. The empirical exercise is based on interactive Generalised Method of Moments. It can be established from the findings that: first, a threshold of 18.072 percentage coverage of public credit registries is needed to counteract the unconditional positive effect of banking system efficiency. Second, on the role of private credit bureaus in financial depth, both the unconditional and the conditional effects are negative; implying a negative synergy. Overall, the findings show that, contingent on the type of financial development dynamic, credit registries broadly play their theoretical role of decreasing financing constraints in order to ultimately reduce inequality.
Keywords: I30; G20; G29; O16; O55; 330; Inequality; Information asymmetry; Financial development; Africa